Value of Interatrial Block for the Prediction of Silent Ischemic Brain Lesions - Çinier, Göksel (J Atr Fibrillation, 2018)
INTRODUCTION: Previous studies demonstrated that interatrial block (IAB) is associated with atrial fibrillation (AF) in different clinical scenarios. The aim of our study was to determine whether IAB could predict silent ischemic brain lesions (sIBL), detected by magnetic resonance imaging (MRI). METHODS: Patients presented to a neurology clinic with transient ischemic attack (TIA) symptoms and underwent brain MRI were included to the study. sIBL were defined as lesions without corresponding clinical symptoms regarding lesion localization evaluated by two neurologists. A 12-lead surface ECG was obtained from each patient. IAB was defined as P-wave duration > 120 ms with (advanced IAB) or without (partial IAB) biphasic morphology in the inferior leads. RESULTS: sIBL was detected in 61 (49.6%) patients. Patients with sIBL were older (P<0.001), had more left ventricular hypertrophy (LVH) (P=0.02) and higher CHA2DS2-VASc score compared to those without (P<0.001). P-wave duration was significantly longer in patients with sIBL (124 [110.5 – 129] msvs 107 [102 – 116.3] ms) (P<0.001). IAB was diagnosed in 36 patients (59%) with sIBL (+) and in 11 patients (18%) with sIBL (-); p<0.001. Multivariate logistic regression analysis identified age [Odds ratio (OR), 1.061; 95% confidence interval (CI), 1.012 - 1.113; p=0.014], CHA2DS2-VASc score (OR, 1.758; 95% CI, 1.045 - 2.956; p=0.034), LVH (OR, 3.062; 95% CI, 1.161 - 8.076; p=0.024) and IAB (including both partial and advanced) (OR, 5.959; 95% CI, 2.269 - 15.653; p<0.001) as independent predictors of sIBL. CONCLUSION: IAB is a strong predictor of sIBL and can be easily diagnosed by performing surface 12-lead ECG.